The unknown known: non-cardiogenic pulmonary edema in amlodipine poisoning, a cohort study. (1st November 2020) - Lindeman, Erik; Ålebring, Jonas; Johansson, Anna; Ahlner, Johan; Kugelberg, Fredrik C.; Nordmark Grass, Johanna
Abstract: Context: Amlodipine is the most common calcium channel blocker (CCB) on the Swedish market, and poison center (PC) consultations for amlodipine overdoses are increasing. The clinical picture is dominated by vasodilation with relative preservation of cardiac function. CCBs selectively dilate vessels on the afferent side of the capillary network which, in states of preserved or increased blood flow may lead to edema formation, including non-cardiogenic pulmonary edema (NCPE). This complication has been considered rare in CCB poisoning. In this cohort study of nineteen amlodipine poisonings with high amlodipine blood levels, the incidence and clinical significance of NCPE in severe amlodipine poisoning are explored. Methods: During 2017–2018 the Swedish PC prospectively encouraged the gathering of blood samples in amlodipine poisonings with symptoms requiring treatment with inotropes or vasopressors. Samples were sent by mail to the Forensic Toxicology Division at the Swedish National Board of Forensic Medicine for screening and quantification of relevant toxicants. Patients with blood amlodipine levels >0.25 µg/mL were included in a cohort whose case details were gathered from medical records and PC-case notes with a special focus on signs of NCPE. Results: Nineteen patients met the blood amlodipine inclusion criteria. Four (21%) died and one patient was treated with VA-ECMO. Nine patients developed NCPE defined as a need for positive pressure ventilation (PPV) while having an echocardiographically normal left ventricular function. Conclusion: In this prospective cohort study of consecutive and analytically confirmed significant amlodipine poisonings NCPE was a common finding occurring in 47% of the whole cohort and in 64% of patients who did not go on to develop complete hemodynamic collapse.